Covalent Triazine Frameworks via a Low‐Temperature Polycondensation Approach. Issue 45 (9th October 2017) - Wang, Kewei; Yang, Li‐Ming; Wang, Xi; Guo, Liping; Cheng, Guang; Zhang, Chun; Jin, Shangbin; Tan, Bien; Cooper, Andrew
Abstract: Covalent triazine frameworks (CTFs) are normally synthesized by ionothermal methods. The harsh synthetic conditions and associated limited structural diversity do not benefit for further development and practical large‐scale synthesis of CTFs. Herein we report a new strategy to construct CTFs (CTF‐HUSTs) via a polycondensation approach, which allows the synthesis of CTFs under mild conditions from a wide array of building blocks. Interestingly, these CTFs display a layered structure. The CTFs synthesized were also readily scaled up to gram quantities. The CTFs are potential candidates for separations, photocatalysis and for energy storage applications. In particular, CTF‐HUSTs are found to be promising photocatalysts for sacrificial photocatalytic hydrogen evolution with a maximum rate of 2647 μmol h −1  g −1 under visible light. We also applied a pyrolyzed form of CTF‐HUST‐4 as an anode material in a sodium‐ion battery achieving an excellent discharge capacity of 467 mAh g −1 . Abstract : Layered allrounder : A novel polycondensation approach enables the construction of covalent triazine frameworks (CTFs) under mild conditions from a wide array of building blocks. The resulting CTFs present a new type of layered material with potential applications in separations, photocatalysis, and energy storage.